2021
DOI: 10.3390/ani11030698
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment for Laboratory Zebrafish—A Review of the Evidence and the Challenges

Abstract: Good practice for the housing and care of laboratory zebrafish Danio rerio is an increasingly discussed topic, with focus on appropriate water quality parameters, stocking densities, feeding regimes, anaesthesia and analgesia practices, methods of humane killing, and more. One area of current attention is around the provision of environmental enrichment. Enrichment is accepted as an essential requirement for meeting the behavioural needs and improving the welfare of many laboratory animal species, but in gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 142 publications
(102 reference statements)
0
53
0
2
Order By: Relevance
“…Certainly, grain size can be an important consideration when providing substrate, for example specific differences in gravel diameter were shown to affect the mortality of rainbow trout fingerlings (Reiser et al ., 2019). Fine‐scale differences in dimensions between enrichment types may contribute to conflicting findings, for example where welfare benefits of PE are found in some but not all studies of zebrafish (Stevens et al ., 2021).…”
Section: Towards a More Refined Understanding Of Pementioning
confidence: 99%
“…Certainly, grain size can be an important consideration when providing substrate, for example specific differences in gravel diameter were shown to affect the mortality of rainbow trout fingerlings (Reiser et al ., 2019). Fine‐scale differences in dimensions between enrichment types may contribute to conflicting findings, for example where welfare benefits of PE are found in some but not all studies of zebrafish (Stevens et al ., 2021).…”
Section: Towards a More Refined Understanding Of Pementioning
confidence: 99%
“…The common arguments of lack of environmental enrichment options for aquatic species often revolve around impact of water quality, potential risk of disease spread due to the bio lm accumulation on the structures, and that diverse environmental enrichment may lead to experimental variation [3]. However, careful selection of the material used to put into the water or use of outside backgrounds will not affect water quality.…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, there is an increasing chance of stress due to dominance among the sh, injuries due to ghting, and possible boredom. Increased cortisol levels can in fact decrease growth rate, fertility, and egg count [3]. In addition, when different types of environmental enrichments were tested to see if there was preference and how the behavior of the sh in the tank changed, results have showed that shaded tanks, barren tanks, PVC material and overcrowding (too many plants) increase stress and/or aggressivity and plastic material (over PVC), shaded refuge, and submerged plant reduced aggressivity and/or cortisol and/or increase behavior diversity [3].…”
Section: Introductionmentioning
confidence: 99%
“…This debate should not be restricted to rodents and shall include avians ( Melleu et al, 2016 ; Campbell et al, 2018 ), reptiles ( Burghardt et al, 1996 ), fishes ( Turschwell and White, 2016 ; Fong et al, 2019 ; Masud et al, 2020 ), and even invertebrate animals ( Ayub et al, 2011 ; Mallory et al, 2016 ; Bertapelle et al, 2017 ; Wang et al, 2018 ; Guisnet et al, 2021 ). We bring two practical examples (or recommendations) of improvements that we (the neuroscientific community) could do: (1) when using animal models we should implement environmental enrichment as the standard in the animal facilities (especially for those animal models that attempt to simulate central nervous system disorders), as raising animals in impoverished environments provides suboptimal sensory, cognitive and motor stimulation, making them too reactive to any kind of intervention (i.e., “noise amplifiers”) ( Nithianantharajah and Hannan, 2006 ); (2) when proposing alternative organisms to study behavior (e.g., zebrafish), we should learn from past and present mistakes (mostly in rodents), keeping in mind the ethological and natural needs of the species ( Branchi and Ricceri, 2004 ; Lee et al, 2019 ; Stevens et al, 2021 ). Importantly, when making these improvements we should carefully respect the species-specific characteristics.…”
Section: Environmental Enrichment In Research Facilities May Favor Translational Neurosciencementioning
confidence: 99%
“…This means that providing running wheels for mice is really necessary, while for rats, (that run less but are more social than mice) ( Kondrakiewicz et al, 2019 ) the space dedicated to some of the running wheels could be better used by increasing (carefully not to compromise the population density) the number of individuals in the home cage. On the other hand, zebrafish needs aquatic plants and several substrates in their environment, such as mud, gravel or sand, to represent their own eco-ethological expansions of behavior ( Engeszer et al, 2007 ; Spence et al, 2008 ; Arunachalam et al, 2013 ; Parichy, 2015 ; Stevens et al, 2021 ). The substrates might provide some camouflage for zebrafish against the predator, which may contribute to feelings of security and improved welfare ( Schroeder et al, 2014 ).…”
Section: Environmental Enrichment In Research Facilities May Favor Translational Neurosciencementioning
confidence: 99%